The Effectiveness of Spotify in Improving the Speaking Skills of Tenth-Grade Students at SMA Negeri 1 Sukawati - I Kadek Yoga Sedana; Ni Putu Ratni; Made Iwan Indrawan Jendra (Educational Journal, 2026)
This study investigates the effectiveness of Spotify-based learning in improving the speaking skills of tenth-grade students at SMA Negeri 1 Sukawati. Speaking is a crucial skill in English as a Foreign Language (EFL), yet students often experience difficulties such as low confidence, limited vocabulary, poor pronunciation, and lack of speaking practice. To address these issues, Spotify-based audio materials, particularly podcasts and narrative stories, were integrated into Task-Based Language Teaching (TBLT) to provide students with authentic English input and meaningful speaking practice. This research employed a quasi-experimental design with a non-equivalent control group involving pre-test and post-test procedures. The sample consisted of 59 students, with 35 students in the experimental group and 24 students in the control group. The experimental group was taught using Spotify-based learning integrated with TBLT, while the control group received conventional instruction. Students’ speaking performance was assessed based on pronunciation, grammar, vocabulary, fluency, comprehension, and content organization. The data were analyzed using the Mann–Whitney U test. The results revealed a significant difference between the two groups, with a p-value of 0.027 (p < 0.05). The experimental group showed greater improvement in speaking performance, with mean scores increasing from 69.34 in the pre-test to 75.34 in the post-test. Among all speaking aspects, comprehension showed the most significant improvement, followed by vocabulary and content organization. These findings indicate that Spotify-based learning is effective in enhancing students’ speaking skills by providing repeated exposure to authentic listening input and supporting active language use through structured speaking tasks. Therefore, Spotify integrated with TBLT can be considered an effective alternative instructional media in EFL speaking classrooms.